Photoluminescence study of Nd3+-doped Si-rich silica films - Breard, David; Gourbilleau, Fabrice; Belarouci, Ali; Dufour, Christian; Rizk, Richard (Oficyna Wydawnicza Politechniki Wrocławskiej, 2006)
Nd3+-doped silicon-rich silicon oxide thin films have been fabricated by reactive magnetron co-sputtering of a pure silica target topped with Nd2O3 chips. The incorporation of silicon excess in the films has been controlled by the hydrogen partial pressure PH2 introduced in the plasma. Photoluminescence experiments have been made at room temperature using a non resonant excitation with Nd3+ ions. The influences of Nd3+ content and PH2 have been studied to improve the Nd3+ emission. Photoluminescence spectra reveal an enhancement of the Nd3+ emission at 0.9 mm and 1.1 mm when silicon nanoclusters and Nd3+ are embedded in a SiO2 matrix.
Optica Applicata, Vol. 36, 2006, nr 2-3, s. 187-192
Keywords: optyka; Nd; Si; nanoclusters Si; energy transfer